PENGARUH ADOPSI E-COMMERCE TERHADAP KEBERHASILAN USAHA (STUDI KASUS PEDAGANG BATIK DI PASAR GROSIR SETONO) - Sulistyorini, Prastuti; Royanti, Nur Ika; Yunianto, Era (BAPPEDA Kota Pekalongan, 2014)
Effective strategies and targeted to business success of companies can be obtained if batik traders adopt e-commerce. According to the model Technology Accepatance Model (TAM) decision to adopt IT users are influenced by perceived usefulness and ease of use. This study aims to explain the effect of the adoption of e-commerce to business success batik traders Setono Wholesale Market. Formulation of the problem in this research is the extent of adoption of ecommerce can provide benefits to batik traders Setono Wholesale Market, determine whether the benefits and ease of use factor significant and positive impact on the adoption of e-commerce, and e-commerce adoption is significant and positive impact on the success of business. The sample used for hypothesis testing are 32 batik traders who already have a personal website. The sampling technique used is pusposive sampling technique. Testing research instruments using validity, reliability, and normality. Testing research hypotheses using regression analysis intervening. T o process the data used SPSS version 17. Results of hypothesis testing shows there is simultaneously a positive significant impact factor and ease of use of the benefits of e-commerce adoption, and there is a significant positive influence the adoption of e-commerce to business success. Keyword : AdoptionE-commerce, TAM Model.